Narsisme sebagai Wujud Eksistensi Diri dalam Novel “My Name is Red” Karya Orhan Pamuk - Irnawan, Raden Dibi (UI Scholars Hub, 2014)
This paper discusses about socio-psychological dimension in paintings pictured in Orhan Pamuk’s novel My Name is Red. The novel shows us fi ne examples about how paintings can be a media of painters who lived in a repressive era of Sultan Murat III which established rigid rules adopted from Islamic principles of how a painting should be done. This idea manifested in the characters’ behaviour, especially Velijan Eff endi, who hold the Islamic or East principles, but dilemmatically fond of Western principles as an aesthetic way of painting. This kind of dilemma born from the presence of East and West principles intertwined in Turkey at the era pictured in the novel. Results determined that Velijan Eff endi is narcistic as a result of his needs to be acknowledged, to exist in his repressed life. He uses his paintings as the media of expressing his needs.